The circadian rhythm: an influential soundtrack in the diabetes story - Hariri, Amirali; Mirian, Mina; Zarrabi, Ali; Kohandel, Mohammad; Amini-Pozveh, Maryam; Aref, Amir Reza; Tabatabaee, Aliye; Prabhakar, Pranav Kumar; Sivakumar, Ponnurengam Malliappan (Frontiers in Endocrinology, 2023)
Type 2 Diabetes Mellitus (T2DM) has been the main category of metabolic diseases in recent years due to changes in lifestyle and environmental conditions such as diet and physical activity. On the other hand, the circadian rhythm is one of the most significant biological pathways in humans and other mammals, which is affected by light, sleep, and human activity. However, this cycle is controlled via complicated cellular pathways with feedback loops. It is widely known that changes in the circadian rhythm can alter some metabolic pathways of body cells and could affect the treatment process, particularly for metabolic diseases like T2DM. The aim of this study is to explore the importance of the circadian rhythm in the occurrence of T2DM via reviewing the metabolic pathways involved, their relationship with the circadian rhythm from two perspectives, lifestyle and molecular pathways, and their effect on T2DM pathophysiology. These impacts have been demonstrated in a variety of studies and led to the development of approaches such as time-restricted feeding, chronotherapy (time-specific therapies), and circadian molecule stabilizers.